A review on thimerosal: an irreplaceable element of long-term immunisation strategy in low income countries - Singla, Ritika; Gupta, Anita K.; Kaur, Anjleen (International Journal of Basic & Clinical Pharmacology, 2017)
Thimerosal, an organic-mercury (Hg) compound containing 49.55% Hg by weight, is added to vaccines as a preservative permitting formulation of multi-dose vaccine vials. Being a derivative of ethylmercury, it has been linked with autism as a possible risk factor based on the assumption that exposure to ethylmercury would have similar neurotoxic effects as another mercurial compound, methylmercury. In 1999, AAP issued a joint statement emphasising the removal of thimerosal from vaccines. Subsequently, several studies have been conducted; those showing positive association between thimerosal exposure and autism have been recognised to be fraught with methodological flaws. On the other hand, many well controlled studies have failed to find any such causal relation and there are others that have clearly demonstrated a much favourable kinetic profile of ethylmercury as compared to methylmercury. Owing to the lack of data, AAP retired its original statement in 2002. Recently, thimerosal has been exempted from regulation by Minamata Convention on Mercury resulting in the continued use of low cost thimerosal containing vaccines in low income countries which cannot afford to run their immunisation program using single dose thimerosal free vaccines, that comparatively cost much higher, as is the case in high income countries. Some bodies view this as a discrimination on the basis of wealth of a nation and have opposed this decision. This review presents various studies regarding the causal association between thimerosal containing vaccines and autism. The current evidence fails to support any such association. Hence this review supports the exemption of thimerosal from regulation and also justifies its use in LICs for uninterrupted vaccination of the most vulnerable population.